Renewable energy its physics, engineering, use, environmental impacts, economy, and planning aspects - Sorensen, Bent. 1941- (Amsterdam ; Boston : Elsevier Academic Press, 2004)
This third edition of Renewable Energy is undoubtedly one of the most complete accounts of the subject, from source through to extraction and use. The book is academically rigorous, but accessible. The author first describes the effect of the sun on the atmosphere and the creation of wind and waves, including the effects of global warming. For each type of renewable energy, from direct solar radiation to wind and biomass, there follows a technical description of the devices that can be used to transform the energy into useful forms. The author explores new solar cell types, including polymer and organic cells, new biofuel processes and new wave energy devices. The final part of the book loos at social and economic aspects of renewable energy the costs of our current fuel bills versus new energy sources, and the difference it could make to developing as well as developed countries. The concept of whole new energy systems based around wind, solar, and other energies is put into a real-life context. Key features include: Reference paths: the reader may follow the general process from source through to distribution, or concentrate on a specific type of energy. The material is divided into undergraduate text and advanced options. Details the significant expansion of the field since the publication of the previous edition. Updated material includes offshore wind technologies, polymer and organic solar cells, new developments in hydrogen storage, pipeline transmission, biofuel processes, and wave energy devices, evaluation of biomass options, and an outlook on the renewable energy market. * The only rigorous theory and applications book available * Provides the principles of renewable energy flows/sources and energy conversion processes * Details the significant expansion of the field since the publication of the previous editions.
Perspectives -- The origin of renewable energy flows -- The individual energy sources -- The energy conversion processes -- Energy transmission and storage -- Energy supply systems -- Socio-economic assessment of energy supply systems -- Winding up.
Includes bibliographical references (p. 877-915) and index.
Keywords: Renewable energy sources; Electronic books